Perfume : - Suskind, Patrick (Penguin Books, 1986)
Perfume takes place in eighteenth-century France and is about a man, Jean-Baptiste Grenouille, who had no scent of his own but had been gifted with the most extraordinary sense of smell. Jean-Baptiste Grenouille was born in 1738 in Paris, in the most horrid conditions, and was abandoned by his mother. Brought up by a succession of wet nurses, he started working for a tanner who, when Grenouille was thirteen, allowed him to go out and wander around the streets of Paris for one hour every day. It was then that Grenouille started his quest for the perfect smell and, with it, began his reign of terror.